Encapsulation of Menthol in Beeswax by a Supercritical Fluid Technique - Linjing Zhu; Hongqiao Lan; Bingjing He; Wei Hong; Jun Li (International Journal of Chemical Engineering)
Encapsulation of menthol in beeswax was prepared by a modified particles from gas-saturated solutions (PGSS) process with controlling the gas-saturated solution flow rate. Menthol/beeswax particles with size in the range of 2–50 μm were produced. The effects of the process conditions, namely, the pre-expansion pressure, pre-expansion temperature, gas-saturated solution flow rate, and menthol composition, on the particle size, particle size distribution, and menthol encapsulation rate were investigated. Results indicated that in the range of studied conditions, increase of the pressure, decrease of the gas-saturated solution flow rate, and decrease of the menthol mass fraction can decrease the particle size and narrow particle size distribution of the produced menthol/beeswax microparticles. An N2-blowing method was proposed to measure the menthol release from the menthol/beeswax microparticles. Results showed that the microparticles have obvious protection of menthol from its volatilization loss.